Design a switch-capacitor DC/DC converter with output voltage regulation - Yang, Jing (2010)
As integrated circuit is being continuously developed, there is a trend for people to pursue products that are portable and able to operate longer per battery charge. Consequently, we conducted a research on switch-capacitor technology to convert variable voltage generated from solar panel to regulated voltage for electrical devices. In this project, firstly we did a general research on Personal Digital Assistant (PDA) size and input/output voltage of battery. Secondly, we designed the switch-capacitor DC/DC converter circuit in transistor level which was based on 0.18 micro CMOS Process Technology. Finally, we used Verilog AMS to simulate the whole gain control system. This report presents the implementation of a switch-capacitor DC/DC converter circuit design, also in VHDL and Verilog programming. Furthermore, we analyze the circuit failure mechanisms and analog/digital signal control problems and overcome these problems.